Perfil cognitivo del trastorno por estrés postraumático agudo en personas víctimas de un atentado con carro bomba en Colombia (2015)
ABSTRACT: The cognitive profile of car bomb victims in Colombia relating to acute post-traumatic stress syndrome is being studied descriptively and transversely. The case group consists of: 16 victims that fall into the criteria of the diagnostics of acute pot-traumatic stress, 8 subjects that witnessed the attack did not meet the requirements and 16 another are the control group. In the three groups we applied the use of the Checklist from DSM-IV and the Mini International Neuropsychiatric Interview to confirm the diagnostic. As well the use of Escala de estrategias de coping modificada (the modified copy of School of Strategies) and the Young Schema Questionnaire Long Form. Between the three groups we encountered significant differences of early maladaptive schemas and copying strategies.